PERENCANAAN PEMBANGUNAN HUTAN KOTA DI KECAMATAN SIGI BIROMARU KABUPATEN SIGI PROVINSI SULAWESI TENGAH - Sungke, Jonar Pranata; Hamzari, .; Dg.Massiri, Sudirman (Universitas Tadulako, 2018)
Urban development planning is to improve the quality and environmental sustainability in the city of Urban Sigi Biromaru Sigi Regency Central Sulawesi Province. This study aims to determine the planning of urban development in Sigi District. The method used in this research is descriptive analysis method by describing and mengintreprestasikan existing condition or relationship. Research on urban development planning in Sigi Regency with Minister of Forestry regulation No.71 / Menhut-II / 2009 on city forest management, technical aspects, economic aspects, ecological, social and cultural aspects. Technical aspects of urban forest of Regency of Sigi has wide of area of 5 Ha with kind of plant of headland, ebony, nyatoh, mahoni with spacing of 3x5 M. Ecological, social and cultural aspect is knowledge and knowledge of society in development which studied memeiliki category